pH-Sensitive PEGylated Liposomes Functionalized With a Fibronectin-Mimetic Peptide Show Enhanced Intracellular Delivery to Colon Cancer Cells - Garg, Ashish; Kokkoli, Efrosini (Current Pharmaceutical Biotechnology, 2011)
pH-sensitive liposomes undergo rapid destabilization under mildly acidic conditions such as those found in endocytotic vesicles. Though this makes them promising drug carriers, their application is limited due to their rapid clearance from circulation by the reticulo-endothelial system. Researchers have therefore used pH-sensitive liposomes that are sterically stabilized by polyethylene glycol (PEG) molecules (stealth liposomes) on the liposome surface. The goal of this study is to bring bio-functionality to pH-sensitive PEGylated liposomes in order to facilitate their potential use as a targeted drug delivery agent. To improve the selectivity of these nanoparticles, we included a targeting moiety, PR_b which specifically recognizes and binds to integrin α5β1 expressing cells. PR_b (KSSPHSRN(SG)5RGDSP) is a novel fibronectin- mimetic peptide sequence that mimics the cell adhesion domain of fibronectin. Integrin α5β1 is expressed on several types of cancer cells, including colon cancer, and plays an important role in tumor growth and metastasis. We have thoroughly studied the release of calcein from pH-sensitive PEGylated liposomes by varying the lipid composition of the liposomes in the absence and presence of the targeting peptide, PR_b, and accounting for the first time for the effect of both pH and time (photo-bleaching effect) on the fluorescence signal of calcein. We have demonstrated that we can design PR_b-targeted pH-sensitive PEGylated liposomes, which can undergo destabilization under mildly acidic conditions and have shown that incorporating the PR_b peptide does not significantly affect the pH-sensitivity of the liposomes. PR_b targeted pH-sensitive PEGylated liposomes bind to CT26.WT colon carcinoma cells that express integrin α5β1, undergo cellular internalization, and release their load intracellularly in a short period of time as compared to other formulations. Our studies demonstrate that PR_b-functionalized pH-sensitive targeted delivery systems have the potential to deliver a payload directly to cancer cells in an efficient and specific manner.
Keywords: photo-bleaching effect